Is a monetary union feasible for Latin America? Evidence from real effective exchange rates and interest rate pass-through levels - McKnight, Stephen; Robles Sánchez, Marco (Estudios Económicos de El Colegio de México, 2014)
This paper assesses the feasibility of forming a common currency in Latin America. First, we examine the cointegration and Granger causality of real effective exchange rates and find evidence supporting a monetary union comprised of Argentina, Bolivia, Brazil, Chile, Colombia, Mexico, and Paraguay. Second, we examine the degree of heterogeneity in the transmission of monetary policy within the hypothetical monetary union. Considerable asymmetries in the pass-through levels of interest rates are found to exist indicating the need for substantial reforms before a Latin American monetary union could take place.